The Effects of Socio-Scientific Approach on Junior High School Students' Learning Outcomes - Rahmadhani, Salsabila Nur; Agustina, Putri; Mulyani, Sri (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
In learning students are expected to get success in learning. One of the factors that can influence the success of student learning is the selection of appropriate learning approaches. The Socio-scientific Issue learning approach is a learning approach that examines facts on an event based on social issues related to science in society. The purpose of this research is to find out and examine the effect of the socio-scientific issue learning approach on junior high school student learning outcomes. This type of research is quasi-experimental with quantitative data and processed using non-parametric statistical data analysis techniques to determine the effect of treatment on the dependent variable by controlling the independent variables. In this study. the results showed that the initial ability of the two groups was 31.8 for the control class and 21.8 for the experimental class. After the experimental class received learning using the Socio-scientific Issue approach. it obtained a better average score than the control class. namely 80.9 for the experimental class and 58.8 for the control class. Based on data analysis and discussion. it can be concluded that the Socio-scientific Issue approach has a significant effect on student learning outcomes.